Effectiveness Efficiency and biochemical content of Physical and Chemical Mutagens in Soybean (Glycine max (L.) Merr.) - D. Dhanavel, P. Pavadai, M. Girija, (Journal of Phytology, 2009)
<span style="font-size: 12pt; font-family: ";Times New Roman";,";serif";; letter-spacing: -0.4pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In a mutation breeding experiment, in the CO-1 variety of soybean (Glycine max (L.) <span style="font-size: 12pt; font-family: ";Times New Roman";,";serif";; letter-spacing: -0.2pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Merr.) the efficiency and effectiveness of physical and chemical mutagens viz., gamma rays, ethyl methane sulphonate (EMS), diethyl sulphate (DES) and Colchicine (COH) were examined. Gamma rays were found to be more effective than other mutagens in producing chlorophyll and viable mutants. The efficiency was observed based on lethality and injury. Gamma rays were found to be more effective than other treatments. The chlorophyll mutants viz., Albino, Viriscence and Xantha and viable mutants viz., plant type, days to maturity, early flowering, seed color, seed shape, pod shape & male sterility etc. were recorded with various frequencies.Ã‚Â The protein and oil content was recorded maximum at 50 KR of gamma rays.Ã‚Â Ã‚Â Ã‚Â